Technology Entrepreneurship : Clate-ZY / Ainin Sofiya Rusfahizan ... [et al.] - Rusfahizan, Ainin Sofiya; Zakaria, Azni Sharlina; Mohd Arif, Nur Izzati; Sauji, Nur Syafika Azreen; Tuan Mohammad, Tuan Nur Najwa (2019)
It is known that people tend to buy a lot of foods and drinks when they go to the night market, by the beach, near the stadium or any places that have the same vibes like the places mentioned. The problems arise when there are so many plastic bags of food and cups of drinks to hold by them. This is not only bring a hard time to the people, but also will ruin their mood when they are about to enjoy their time since they are uncomfortable with the situation. Besides, the usage of plastic bags and cups are really bad for the environment. Thus, this study was conducted to develop a product that will ease customers to hold their foods and drinks as well as saving our environment by developing a biodegradable products. It also discovers how many potential consumers are interested in the product. Also, this paper will highlight the design of the product and reasoning behind the parameters chosen.